(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The frantic fight for admission to ―Indian Institutes of Technology, Indian Institutes ofManagement and other prestigious foundations is about to inspire many stunts to master, especially inscience and arithmetic. Currently, only a small fraction of the appropriate age is enrolled in highereducation, showing that the growing interest in higher education is not being met. In any case, in acountry with such a colossal population, 10 of enrollment equates to 9 million college students,generating around 2.5 million new graduates each year‖. Before the British went to India, the conventionalschool system prevailed However, the current status of the constitution was conferred on India by theEast India Company around 1813 through the remarkable Charter Act. From that point on, the East IndiaCompany and the British government formed various commissions and committees to make educationavailable to all However, some of the commissions and committees would have been successful andsome of them could not have been successful due to lack of effort, funding, government strategy, publicawareness, and other reasons. Likewise, after India’s independence, the Indian government found a wayto guarantee education for all or allow people to attend training for a fee or sometimes for free